Incidence of atrial fibrillation in acute respiratory emergency and exacerbation of chronic lung disease - Wsw, Sarhang Sidiq; Karadakhy, Kamaran Amin (Journal of Neonatal Surgery, 2025)
Background and Objectives: Atrial fibrillation (AF), a prevalent arrhythmia linked to mortality, demonstrates a bidirectional relationship with chronic lung diseases like chronic obstructive pulmonary disease, asthma, pulmonary fibrosis due to shared mechanisms such as hypoxia and inflammation. Acute respiratory emergencies further exacerbate this risk. This study aimed to determine the incidence of AF in patients with acute respiratory emergencies or chronic lung disease exacerbations in Sulaimaniyah, Iraq. Methods: An observational cross-sectional study was conducted at Shar Teaching Hospital from 1stMarch 2024 to 28th February 2025. A convenience sample of 100 adult’s patient admitted with acute respiratory emergencies or chronic lung disease exacerbations underwent a12-lead ECG at the time of admission. Results: AF was detected in 14% of patients on admission. The mean age was 60.4 ± 14.3 years, and 58% were female. AF was more frequent in patients with COPD (20%) and obstructive sleep apnea (OSA, 42.9%), as well as in those with higher C-reactive protein (CRP) levels and lower oxygen saturation (SpO₂) on admission (p=0.001 and p=0.012, respectively). Most AF cases were transient, resolving by discharge in all but one patient. No significant associations were found between AF and age, sex, or smoking status. Conclusion: AF is a notable and often transient complication in patients with acute respiratory emergencies, particularly among those with COPD, OSA, hypoxemia, and elevated inflammation. Routine monitoring for AF is recommended in high-risk respiratory patients